Implementation of environmental life cycle assessment model in organic municipal solid waste management in Malaysia / Ng Chee Guan - Ng, Chee Guan (2016)

(untitled)
Organic Municipal Solid Waste (OMSW) generation in Malaysia is overwhelming and most of the waste generated ended up in the waste stream to be disposed in landfills. However, there has been minimal research on the comprehensive evaluation of the Malaysian OMSW management system from environmental perspective despite priority being given to increase recycling rate and composting of OMSW by the Malaysian government. The main aim of the thesis is to study the environmental benefits of OMSW management. The objectives include: (1) to determine the characteristics and elemental composition of OMSW generated in Malaysia; (2) to provide a comprehensive Life Cycle Inventory (LCI) of medium scale co-composting of OMSW; (3) to evaluate environmental impacts and benefits associated with alternative OMSW management system; and (4) to quantify the total CO2 equivalent reduction potential from OMSW recycling via composting as compared to landfilling (Business-as-Usual) in Peninsular Malaysia. A comprehensive Life Cycle Inventory (LCI) of medium scale co-composting of OMSW was carried out based on comprehensive field studies. Substance Flow Analysis of C, N, P, K, Cd, Cr, Cu, Ni and Pb were carried out by using STAN 2.5 software. The inputs and outputs of OMSW composting process were also recorded. The life cycle environmental impacts from alternative OMSW management system were evaluated based on ISO 14000 series. The total CO2 equivalent reduction potential from OMSW recycling via composting as compared to landfilling was assessed through scenarios comparison in accordance to Malaysian municipal solid waste management strategic plan. The LCI of medium-scale co-composting of OMSW in tropical environment was presented. The C/N reduction during the process was in the range of 10-23%. In general, the compost composition was considered to be within the ranges previously reported in literature. Heavy metals were found to remain in the finished compost where the release of heavy metal to atmosphere is insignificant. No iv major environmental problems were identified from the OMSE composting process, except for the emissions of GHGs. LCA studies revealed that anaerobic digestion is the most environmentally sound management for OMSW with net environmental gain whereas disposal of OMSW at landfill are generally less environmental favourable. This study also highlights the importance of decomposition emissions control during OMSW composting, particularly CH4, N2O and NH3. OMSW diversion from disposal created significant climate change benefits in term of net GHG emissions reduction. The current study reveals that an additional of 21% GHG emissions reduction including the recycling of OMSW via composting in all sectors, on top of 25.5% GHG emission reduction from Malaysia waste by increasing the recycling rate to 22% as reported by previous study. A knowledge-based goal-oriented OMSW management study is necessary to analyse the state-of-art of OMSW management in Malaysia and direct it towards fulfilling the main goals of waste management. The results provide information of all significant inputs and outputs in the form of elementary flow to and from the environment from OMSW management involved. Based on the experience of SFA in the present study, the emissions quantified are likely to be in agreement with that from previous studies. Hence, author agrees and advocates that SFA is able to be integrated with LCI and eventually LCIA studies upon OMSW management sector in Malaysia.